Methodology of excavator system energy flow-down - An, Kwangman; Kang, Hyehyun; An, Youngkuk; Park, Jinil; Lee, Jonghwa (Energies, 2020)
Due to the strengthening of air-quality regulations, researchers have been investigating methods to improve excavator energy efficiency. Many researchers primarily conducted simulation studies employing mathematical models to analyze the energy consumption of excavator systems, which is necessary to examine the fuel efficiency improvement margin and the improvement effect. However, to effectively study the improvement of excavator efficiency, the real-time energy consumption characteristics must be examined through simulations and analyses of actual equipment-based energy consumption. Accordingly, this study establishes an energy flow-down model for the entire excavator system based on actual equipment tests. A measurement system is built to measure the required data, thereby establishing an experimental methodology for modeling each component. This paper presents an excavator system energy flow-down methodology that integrates the energy flow-down model, measurement system, and experimental methodology. This methodology was applied to dig and dump operations, and the energy consumption characteristics were analyzed. An analysis of the operating modes indicates that 59.8% of the total fuel energy was consumed in the engine system, 17% in the hydraulic system, and 23.2% in the hydraulic actuation systems. The methodology can be used to help analysis of the fuel efficiency improvement margin under various conditions.
Keywords: Energy flow; Engine systems; Hydraulic actuation systems; Hydraulic excavator; Hydraulic system; Energy consumption; Energy flow down; Engine system; Hydraulic actuation system; Hydraulic excavator; Hydraulic system